Response to and toxicity of gemcitabine for recurrent ovarian cancer according to number of previous chemotherapy regimens. Issue 2 (9th December 2016) - Takei, Yuji; Takahashi, Yoshifumi; Machida, Shizuo; Taneichi, Akiyo; Takahashi, Suzuyo; Nagashima, Tomomi; Morisawa, Hiroyuki; Saga, Yasushi; Matsubara, Shigeki; Fujiwara, Hiroyuki
Abstract: Aim: Gemcitabine is used not only as a second‐line, but also as a third‐line or higher regimen for taxane/platinum‐resistant recurrent ovarian cancer. The purpose of this study was to clarify the response to and toxicity of gemcitabine for recurrent ovarian cancer according to the number of previous chemotherapy regimens. Methods: The subjects were patients with taxane/platinum‐resistant recurrent ovarian cancer on gemcitabine treatment at the present hospital between June 2007 and September 2013. We retrospectively reviewed the medical records. Response and adverse events were assessed using the Response Evaluation Criteria in Solid Tumors version 1.1. and the Common Terminology Criteria for Adverse Events v4.0, respectively. Results: The subjects consisted of 65 patients. The median number of previous chemotherapy regimens was 3 (range, 1–7). Overall response rate was 4.6%, and disease control rate (DCR) was 40.0%. DCR versus one, two, three, and ≥four previous chemotherapy regimens was 83.3%, 45.0%, 36.4%, and 23.5%, respectively. Grade 3/4 neutropenia, anemia, and thrombocytopenia occurred in 52.3%, 9.2%, and 9.2% of patients, respectively. Prevalence of grade 3/4 neutropenia according to one, two, three, and ≥four previous chemotherapy regimens was 66.7%, 55.0%, 54.5%, and 41.2%, respectively. Prevalence of anemia, thrombocytopenia, and almost all the non‐hematological toxicities also did not increase with an increase in the number of previous chemotherapy regimens. Conclusions: Although DCR decreased as the number of previous chemotherapy regimens increased, the toxicities did not increase. Gemcitabine may be relatively safe in heavily pretreated ovarian cancer patients.